SIMBOLISME ARSITEKTUR TIMUR TENGAH PADA BANGUNAN MASJID DI INDONESIA - retno astuti (Jurnal Pelita Teknologi, 2018)
Symbols are terms that have been known to people in the world, human life can not be separated from the concept of symbolism. Symbols are manifested in images, shapes, movements, or objects that represent an idea. Symbols can lead a person into future and past ideas. This is evident from the existence of historical relics that exist in all parts of the world from time to time. Humans can be recognized by their civilization starting with the symbols or symbols they leave behind. These symbols have a specific purpose and meaning which is an appreciation of the values they represent. Symbols consist of signs (tangible) and meanings (intangible). These two elements in symbolism are an inseparable unit. There is no sign that does not have the opposite meaning there is no meaning that can be understood by others if it is not a sign. In the science of architecture the process of creating architectural works is analogous to the process of creating symbols. There are no architectural works born without ideas, and vice versa, not an architect's ideas will materialize if they do not have a real form. Middle Eastern architecture that is synonymous with Islam has a symbol that has been understood by most Muslims throughout the world. The application of the symbolism of the Middle East architecture is mostly in the mosque building, which is a place of worship for all Muslims. This Middle Eastern architectural symbol successfully unites all Muslims throughout the world.